DESKRIPSI KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS DITINJAU DARI GAYA BELAJAR SISWA - Muhammad Rizal Usman; Baharullah Baharullah; Kristiawati Kristiawati (JURNAL MathEdu (Mathematic Education Journal), 2022)
This research is a descriptive qualitative research that aims to describe students' mathematical conceptual understanding in terms of visual, auditory, and kinesthetic learning styles. The subjects of this study were 3 seventh grade students at MTS Guppi Rannaloe Kab. Gowa, each of which represents: visual, auditory, and kinesthetic learning styles. The data in this study were obtained using research instruments, namely (1) the researcher himself; (2) learning style questionnaire; (3) concept understanding ability test; and (4) interview guidelines. The data analysis technique used is qualitative data analysis techniques, including: (1) data condensation, (2) data presentation, and (3) drawing conclusions and verification. From the results of this study it can be concluded that; (1) students with visual learning styles are able to fulfill 2 indicators, namely giving examples and non-examples of concepts, and expressing concepts in various forms of mathematical representation; (2) students with auditory learning style do not meet any of the indicators; (3) students with kinesthetic learning styles are able to fulfill 2 indicators, namely giving examples and non-examples of concepts, and expressing concepts in the form of mathematical representations.